Study guides

☆☆

Q: What does y equals 9x equals 3 equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-9x+6=y (swap over +6 and y) -9x-y=-6 (when u move numbers or letters over d equal sign u need 2 change signs) 9x+y=6 (chaned all signs) y= 6-9 y= -3 9x+y=6 9x+-3=6 9x=6+3 9x=9 x=9(divided by) 9 x=1 9x+y=6 9+-3=6 So the ordered pair is (1,-3)

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

3x-3y=-9 and 9x-9y=-27 both simplifies to x-y=-3.

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

9x + 3y = -54 3y = -9x - 54 y = -(3x + 18) Therefore, the y-intercept of this equation is y=-18.

Related questions

-9x+6=y (swap over +6 and y) -9x-y=-6 (when u move numbers or letters over d equal sign u need 2 change signs) 9x+y=6 (chaned all signs) y= 6-9 y= -3 9x+y=6 9x+-3=6 9x=6+3 9x=9 x=9(divided by) 9 x=1 9x+y=6 9+-3=6 So the ordered pair is (1,-3)

The y intercept would be 3.

9x + 8y = (9 x 6) + (8 x 3) = 54 + 24 = 78

2y - 9x = 14 2y = 14 + 9x y = (14 + 9x) / 2

If x equals 10 and y equals 10, then 9x plus 8y equals 170.

Multiply the first equation by 3 to give 9x + 15y = 21

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

In the equation y = mx + b, m is the slope. To convert 9x - 3y = 10 to y = mx + b: 9x - 3y = 10 Subtract 9x from both sides: -3y = -9x +10 Divide both sides by -3: y = 3x - 10/3 The slope of this line is 3.

3x-3y=-9 and 9x-9y=-27 both simplifies to x-y=-3.

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

No because they don't have the same slope (9x & 3x)

9x + 3y = -54 3y = -9x - 54 y = -(3x + 18) Therefore, the y-intercept of this equation is y=-18.